Using the Structure of Evaluative Components as a basis for comparing the oral narratives of schizophrenics and healthy individuals - Shafiyan, Sina; Izanloo, Ali; Yazdi, Amir Amin (Journal of psycholinguistic research, 2022)
In this study, evaluative language in narratives of 15 healthy and 15 schizophrenic females was compared using the Structure of Evaluative Components. The two groups were matched for chronological age and socioeconomic status. A movie named “The Pear Film” ( http://chafe.faculty.linguistics.ucsb.edu/pearfilm.htm ) was used to elicit the narratives. The Goal evaluative component in the schizophrenic population and the Ownership in healthy individuals were used more than other components within the narratives of each respective group. Significant differences (Mann-Whitney and t-test) between the two groups in using evaluative components were determined using statistical analysis. In general, patients used less evaluative components in their narratives compared to healthy participants and as per specific components, healthy subjects utilized five evaluative components more than patients, which was found to be a significant difference; Goal, Assumption, Ownership, Metaphor, and Causality were those five components. These findings confirm that the ability to use evaluative language in schizophrenia is reduced.